MODEL PENDAMPINGAN DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK (DP3A) DALAM MENANGANI KEKERASAN PADA ANAK DI BAWAH UMUR DI KECAMATAN SOMBA OPU KABUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
The main problem of this research is how the factors that cause the practice of violence against minors in the Somba Opu sub-district, Gowa district, and how the model of assistance carried out by the Women's Empowerment and Protection Service in dealing with violence against minors in the Somba Opu sub-district, Gowa district. The results of this study indicate that: 1. Factors causing violence against minors are: a) economic factors b) lack of family education c) environmental factors d) child delinquency factors. 2. Mentoring models, namely: a) early-stage mentoring model b) second-stage mentoring model c) late-stage mentoring model.